(untitled) (Fiep Bulletin - online, 2012)
The Down’s Syndrome, a genetic modification brought about by chromosomal abnormalities, is affecting people worldwide with increasingly high rates, either due to the achievement of independence for women, depending on the autonomy of those seeking a more propitious moment, financially to generate a child, which implies and pregnancies at ages older, or because of technological advances that allowed for clarification in terms of a reduction of prejudice, so that people submit their children suffering from Down syndrome to society more easily . Thus, more studies are conducted for a better quality of life for these individuals, aiming findings of methodologies that allow a greater longevity for the same. It is known that despite the moderate cognitive limitations, they have difficulty coordinating body, motor skills and strength levels, as well as joint hypermobility, high levels of fat percentage and the inefficient coordination. These are just some of the changes that hinder the full development of these individuals engine. One of the methodologies that enable the improvement of strength as well as control and coordination body, and thanks to high energy costs as a result of interval training is weight training, which when applied in these individuals could generate body changes, within a margin of security related to the limitations of these people with the syndrome. Thus this study as a literature review of the database as the Siel, Medline and Lilacs, was aimed at seeking research methodology as that used om Training Weights applied specifically to this group. Thus obtained as a result, considerable changes both in levels of body strength and coordination, such as changes in body composition of people with Down syndrome.